Dual targeting of insulin and venus kinase Receptors of Schistosoma mansoni for novel anti-schistosome therapy. - Mathieu Vanderstraete; Nadège Gouignard; Katia Cailliau; Marion Morel; Julien Lancelot; Jean-François Bodart; Colette Dissous (Public Library of Science (PLoS), 2013)
BACKGROUND: Chemotherapy of schistosomiasis relies on a single drug, Praziquantel (PZQ) and mass-use of this compound has led to emergence of resistant strains of Schistosoma mansoni, therefore pointing out the necessity to find alternative drugs. Through their essential functions in development and metabolism, receptor tyrosine kinases (RTK) could represent valuable drug targets for novel anti-schistosome chemotherapies. Taking advantage of the similarity between the catalytic domains of S. mansoni insulin receptors (SmIR1 and SmIR2) and Venus Kinase Receptors (SmVKR1 and SmVKR2), we studied the possibility to fight schistosomes by targeting simultaneously the four receptors with a single drug. METHODOLOGY/PRINCIPAL FINDINGS: Several commercial RTK inhibitors were tested for their potential to inhibit the kinase activities of SmIR1, SmIR2, SmVKR1 and SmVKR2 intracellular domains (ICD) expressed in Xenopus oocytes. We measured the inhibitory effect of chemicals on meiosis resumption induced by the active ICD of the schistosome kinases in oocytes. The IR inhibitor, tyrphostin AG1024, was the most potent inhibitory compound towards SmIR and SmVKR kinases. In vitro studies then allowed us to show that AG1024 affected the viability of both schistosomula and adult worms of S. mansoni. At micromolar doses, AG1024 induced apoptosis and caused schistosomula death in a dose-dependent manner. In adult worms, AG1024 provoked alterations of reproductive organs, as observed by confocal laser scanner microscopy. With 5 µM AG1024, parasites were no more feeding and laying eggs, and they died within 48 h with 10 µM. CONCLUSION/SIGNIFICANCE: IRs and VKRs are essential in S. mansoni for key biological processes including glucose uptake, metabolism and reproduction. Our results demonstrate that inhibiting the kinase potential and function of these receptors by a single chemical compound AG1024 at low concentrations, leads to death of schistosomula and adult worms. Thus, AG1024 represents a valuable hit compound for further design of anti-kinase drugs applicable to anti-schistosome chemotherapy.